Answer:
[See Below]
Step-by-step explanation:
✦ Combine like terms:
✧ -5n + 2n = -3n
✦ Rewrite:
✧ 3 < -3n
✦ Divide:
✧ 3 / -3 = -1
So n = -1.
~<em>Hope this Helps Mate. If you need anything feel free to message me. </em>
Answer:
Step-by-step explanation:
If two triangles are congruent, then the corresponding sides and angles are congruent with each other.
<u>Given:</u>
<u>The following are congruent parts:</u>
- ∠E ≅ ∠U
- RE ≅ SU
- ∠DRE ≅ ∠NSU
- ∠R ≅ ∠S
<u>Note</u> <em>Pay attention to order of vertices when comparing the congruent parts</em>
Answer:
Step-by-step explanation:
A. Two measurements(AandB)are taken on the same round.\oIs there a difference in the measurement of the muzzle velocity between device A and device B at the α=0.01 level of significance? Note: A normal probability plot and boxplot of the data indicate that the differences are approximately normally distributed with no outliers.
B. Construct a 99% confidence interval about the population mean difference. Compute the difference as device A minus device B. Interpret your results. The confidence interval is (__,__)?
Answer:
Open chart in StatCrunch --- Stat --- T Stats --- Paired --- Enter values: Sample 1 = A, Sample 2 = B --- Click on Confidence Interval… and enter Level which is my #%. --- Compute
5.49 $, just add them altogether
Answer:
The solution to the system is
,
and
Step-by-step explanation:
Cramer's rule defines the solution of a system of equations in the following way:
,
and
where
,
and
are the determinants formed by replacing the x,y and z-column values with the answer-column values respectively.
is the determinant of the system. Let's see how this rule applies to this system.
The system can be written in matrix form like:
![\left[\begin{array}{ccc}5&-3&1\\0&2&-3\\7&10&0\end{array}\right]\times \left[\begin{array}{c}x&y&z\end{array}\right] = \left[\begin{array}{c}6&11&-13\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D5%26-3%261%5C%5C0%262%26-3%5C%5C7%2610%260%5Cend%7Barray%7D%5Cright%5D%5Ctimes%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7Dx%26y%26z%5Cend%7Barray%7D%5Cright%5D%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7D6%2611%26-13%5Cend%7Barray%7D%5Cright%5D)
Then each of the previous determinants are given by:
Notice how the x-column has been substituted with the answer-column one.
Notice how the y-column has been substituted with the answer-column one.
![D_z = \left|\begin{array}{ccc}5&-3&6\\0&2&11\\7&10&-13\end{array}\right|=-995](https://tex.z-dn.net/?f=D_z%20%3D%20%5Cleft%7C%5Cbegin%7Barray%7D%7Bccc%7D5%26-3%266%5C%5C0%262%2611%5C%5C7%2610%26-13%5Cend%7Barray%7D%5Cright%7C%3D-995)
Then, substituting the values:
![x= \frac{D_x}{D}=\frac{199}{199}\\ x=1](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7BD_x%7D%7BD%7D%3D%5Cfrac%7B199%7D%7B199%7D%5C%5C%20x%3D1)
![x= \frac{D_y}{D}=\frac{-398}{199}\\ y=-2](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7BD_y%7D%7BD%7D%3D%5Cfrac%7B-398%7D%7B199%7D%5C%5C%20y%3D-2)
![x= \frac{D_z}{D}=\frac{-995}{199}\\ x=-5](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7BD_z%7D%7BD%7D%3D%5Cfrac%7B-995%7D%7B199%7D%5C%5C%20x%3D-5)